PERAN KELUARGA KRISTIANI SEBAGAI ECCLESIA DOMESTICA DALAM MENUMBUHKAN HABITUS BERDOA BAGI ANAK-ANAK DI STASI MANDAM - Adventura Mario Febiyanto Londa; Silvester Adinuhgra (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2022)
This study aims to describe the role of Christian Families as Ecclesia Domestica in growing the habit of praying children at Stasi St. Maria Manikam Damai Mandam. This research is based on the problem of difficulty in praying experienced by children at the stasi. In this case, the family actually has a role as Ecclesia Domestica (Church-Family), which is a place for children to learn to persevere in prayer, through the habit of praying together in family. This study uses a qualitative approach with a descriptive method. The research data was obtained by using the interview method which was carried out together with 5 couples, 5 teenagers, 1 priest, and 1 nun. The data obtained were analyzed using the “Miles and Hubberman” analysis method, which was divided into three stages, namely reduction, data presentation, and drawing conclusions. Based on the results of the study, it was concluded that the role of Christian families in fostering the habit of praying for children at Stasi St. Maria Manikam Damai Mandam has not been implemented optimally. This conclusion is based on the statements of the informants who revealed that they often experience obstacles caused by the busyness of their parents at work, so they do not have time to pray together in the family or to accompany the children in praying. In addition, other factors that also influence are not yet rooted in the Christian tradition and the lack of parental education. Thus, the role to cultivate the habit of praying is carried out by advising and reminding each other.